Effects of spray adjuvants and operation modes on droplet deposition and elm aphid control using an unmanned aerial vehicle - Dou, Zechen; Fang, Zhihao; Han, Xiaoqiang; Zeeshan, Muhammad; Liu, Yapeng; Lan, Yubin (International Journal of Agricultural and Biological Engineering, 2023)
A conventional spraying mode and a fully autonomous fruit tree operation mode using a model DJ T30 unmanned aerial vehicle (UAV) were used to control aphids control on elm trees and to clarify the distribution of droplets in elm trees sprayed by an UAV. The effects of six aviation spray adjuvants on elm canopy droplet deposition and aphid control were evaluated. ImageJ software was used to analyze and measure the droplet density and deposition of water sensitive paper in two modes; this was done to calculate the droplet uniformity, depositional penetration and droplet penetration, and to verify the aphid control effect. The results showed that the droplet density increased by 79.7%-100.7% in the upper canopy and 0-394.1% in the lower canopy without adjuvants in the fully autonomous fruit tree operation mode. The upper canopy deposits increased by 65.7%-179.3%, and the lower canopy increased by 0-152.8%. When adjuvants were added, the droplet density in the upper canopy increased by 49.7-56.1% using Jiexiaofeng (JXF), and the lower canopy increased by 138.2%-177.8% using JXF, 45.8%-141.3% using Beidatong (BDT), 45.5%-92.9% using Gongbei (GB), 0-93.5% using Maisi (MS), and 0-95.2% using Manniu (MN). The deposits of the upper canopy increased by 888.1-1154.2% using JXF, 0-1298.3% using MN, 0-343.9% using BDT, 0-422.5% using GB, 0-580.3% using MS. The lower canopy increased by 746.4%-1426.0% using JXF, 226.2%-231.0% using BDT, 435.8%-644.0% using GB, 255.0%-322.4% using MS, and 249.3%-360.0% using MN. When JXF was added, the droplet uniformity, droplet penetration and depositional penetration were better than when using other adjuvants. The effects of JXF, BDT and GB in controlling aphids was significantly better than other adjuvants (p<0.05). The following control effects were observed; 94.1% with JXF, 93.1% with BDT, and 93.3% with GB after 3 d of application, and 97.9% with JXF, 95.6% with BDT, and 97.1% with GB after 7 d of application. At the same time, the application of the fully autonomous fruit tree operation mode and JXF can effectively improve the density and deposits, which will produce a superposition optimization effect. Our study focuses on the prevention and control of elm aphid infestations based on the operation mode of a UAV and aviation spray adjuvants, which can provide a baseline for the control of diseases and insect pests using UAVs in agriculture and forestry. Keywords: adjuvants, UAV, operation mode, droplet deposition, aphid DOI: 10.25165/j.ijabe.20231602.7424 Citation: Dou Z C, Fang Z H, Han X Q, Zeeshan M, Liu Y P, Lan Y B. Effects of spray adjuvants and operation modes on droplet deposition and elm aphid control using an unmanned aerial vehicle. Int J Agric & Biol Eng, 2023; 16(2): -.